Person-centered counseling with Malay clients: spirituality as an indicator of personal growth - Mohamad, Mardiana; Mokhtar, Halimatun Halaliah; Abu Samah, Asnarulkhadi (Elsevier, 2011)
A qualitative study was carried out to explore the inner experiences and personal growth of one male and three female Malay university student clients undergoing twelve sessions of person-centered counseling. Data analysis was based on the verbatim accounts of the counseling sessions, Interpersonal Process Recall (IPR) interviews, clients’ journal entries and their non-verbal expressions throughout the sessions. The findings manifest that in the non-directive, egalitarian and person-centered counseling relationship, constructive changes were experienced by the Malay clients in the study, including getting in touch with their religious realization.